Experiences of Female Adolescent on Online Sexual Abuse and Exploitation of Children During Community Quarantine in Davao City, Philippines - Dela Rosa, Maria Teresa Casaysay; Lopez, Sheryl R.; Melba L. Manapol (Asean Social Work Journal, 2023)
The study sought to describe the experiences of female adolescents, ages 15 to 17 years old as victim-survivors of Online Sexual Abuse and Exploitation of Children (OSAEC) during community quarantine in Davao City. The study’s design was descriptive- qualitative particularly phenomenological research. Using purposive sampling the team interviewed eleven female adolescents, three barangay officials for key informant interviews, and conducted a focus group discussion among the identified agencies with direct services for OSAEC. The study describes poverty as the major driving factor that leads female adolescents in Davao City to engage in OSAEC. This situation was further exacerbated when the COVID lockdown happened to result in the loss of jobs, limited mobility, and uncertainty. Consequently, the respondent's family had difficulty sustaining their daily needs, pushing victim-survivors to engage in OSAEC. Limited mobility, caused many respondents to shift to online platforms as substitutes for physical communication, further raising their vulnerability to online sex predators. Respondents were introduced to OSAEC through seemingly harmless online chat groups which eventually led to pimping and matching with potential perpetrators. The chat groups paved the way for new acquaintances with experience in online sexual transactions and pushed victim-survivors to the trade in hopes of gaining financial rewards. Sexual behavior online eventually leads to physical interaction with local perpetrators. The study further revealed that barangay officials have little knowledge and capability in handling OSAEC cases. OSAEC in its many forms continues to victimize children, more so when several factors create vulnerability in them such as naivety, peer pressure, distorted perspectives on filial obligations, minimal awareness, and proactive action from duty-bearers. As we strive to protect the youth from all forms of sexual abuse, there is a greater challenge in providing holistic, multi-disciplinary, and multi sectoral action among duty bearers to stop OSAEC further.